Evangélicos no Congresso: uma análise da atuação da Frente Parlamentar Evangélica na Câmara dos Deputados durante a 55ª Legislatura (2015-2019) - Serrano, Rodrigo Fagundes Luz (2020)
The Evangelical Group in the Chamber of Deputies, organized as the Evangelical Parliamentary Front of the National Congress during the 55th Legislature (2015-2019), with 199 Federal Deputies and 4 Senators in its composition, has gained a lot of power in recent years, especially after the election of 2014, with great pressure to approve projects on its agenda, making use of politics as a way of affirming Christian morals on private customs. This group has gained a lot of influence in recent years through an electoral strategy that maximized the number of elected Federal Deputies aligned with their Christian beliefs through the proportional system and a parliamentary performance in alliance with other groups, especially the ones of public security and agribusiness, in addition to the meticulous use of rules on the Internal Regulations of the Chamber of Deputies. The analysis of its performance in bills publicly sponsored by this parliamentary front showed their alignment with a conservative agenda in the customs and a liberal in the economy. In a deeper study, three paradigmatic votings were considered in the Chamber of Deputies that show an alignment among its members around the reduction of the criminal majority, the impeachment of Dilma Rousseff and the labor reform, with a lower degree of cohesion in the latter. To clarify the positions of this group and to trace future trends, the work ends with observations on the “Manifest to the Nation”, a document published at the end of the 55th Legislature by the Evangelical Parliamentary Front. The study of how these parliamentarians were elected and their behavior in the National Congress is of great importance for the understanding of the Brazilian political scenario, with changes that are underway and possible legislative changes to come.